Correlation between basic sanitation and acute diarrheal diseases in the State of Pará (Research, Society and Development, 2024)
Basic sanitation services are essential for environmental preservation and public health. However, the northern region of Brazil, especially the state of Pará, faces a deficiency in the supply of these services, resulting in an increase in hospitalizations for diseases related to inadequate environmental sanitation, especially acute diarrheal diseases. Given this scenario, the aim of this study was to investigate the correlation between basic sanitation conditions and hospitalizations for Acute Diarrheal Diseases in the thirteen health regions of the state of Pará, from 2014 to 2022. This is a descriptive study based on data from the National Sanitation Information System and the Notifiable Diseases Information System. It was observed that in the period analyzed, the highest number of hospitalizations occurred in 2014, with 23,480 records, and the lowest in 2022, with 9,767 cases. Among the state's health regions, Metropolitana I had the highest number of hospitalizations, while Marajó I and Xingu recorded the lowest numbers. The results of the statistical tests indicated that the indicators with the most significant correlation between the regions were associated with the Operational and Quality of Water Supply Services categories. It is therefore essential to emphasize the need for improvement in the provision of these services by the providers, guaranteeing not only their availability, but also their quality, in order to comply with the legislation in force in the country and preserve the health and well-being of the population and the environment.